Emergent patterns of collective cell migration under tubular confinement. Issue 1 (December 2017) - Xi, Wang; Sonam, Surabhi; Beng Saw, Thuan; Ladoux, Benoit; Teck Lim, Chwee
Abstract Collective epithelial behaviors are essential for the development of lumens in organs. However, conventional assays of planar systems fail to replicate cell cohorts of tubular structures that advance in concerted ways on out-of-plane curved and confined surfaces, such as ductal elongation in vivo. Here, we mimic such coordinated tissue migration by forming lumens of epithelial cell sheets inside microtubes of 1–10 cell lengths in diameter. We show that these cell tubes reproduce the physiological apical–basal polarity, and have actin alignment, cell orientation, tissue organization, and migration modes that depend on the extent of tubular confinement and/or curvature. In contrast to flat constraint, the cell sheets in a highly constricted smaller microtube demonstrate slow motion with periodic relaxation, but fast overall movement in large microtubes. Altogether, our findings provide insights into the emerging migratory modes for epithelial migration and growth under tubular confinement, which are reminiscent of the in vivo scenario. Collective epithelial behaviours are studied in vitro in the context of flat sheets but a system to mimic tubular systems is lacking. Here, the authors develop a method to study collective behaviour in lumenal structures and show that several features depend on the extent of tubular confinement and/or curvature.